2014
DOI: 10.1007/s00464-014-3874-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-curative endoscopic resection does not always lead to grave outcomes in submucosal invasive early gastric cancer

Abstract: Non-curative resection in SM-GC does not always lead to cancer recurrence. Thus, if additional surgery cannot be performed because of the patient's unsuitable condition or refusal, a close follow-up with endoscopy can be considered as an alternative for carefully selected patients. Moreover, as the ESD technology continues to evolve, it might be possible to expand the criteria for curative ESD in patients with SM-GC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 22 publications
(21 reference statements)
2
37
0
Order By: Relevance
“…Although several studies have described the clinical outcomes of noncurative gastric ER patients, the definition of noncurative gastric ER differs between studies; most of these studies have assessed the clinical outcomes of noncurative gastric ER patients in small numbers of patients without detailed statistical analysis [15][16][17][18][19][20][21][22][23][24][25]. For example, noncurative gastric ER was defined according to the Japanese gastric cancer treatment guidelines in some studies but was defined according to the original criteria in others [4,[15][16][17][18][19][20][21][22][23][24][25]. In addition, with the exception of two studies by Oda et al [15] and Yang et al [16], fewer than 200 noncurative gastric ER cases were included in previous studies [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although several studies have described the clinical outcomes of noncurative gastric ER patients, the definition of noncurative gastric ER differs between studies; most of these studies have assessed the clinical outcomes of noncurative gastric ER patients in small numbers of patients without detailed statistical analysis [15][16][17][18][19][20][21][22][23][24][25]. For example, noncurative gastric ER was defined according to the Japanese gastric cancer treatment guidelines in some studies but was defined according to the original criteria in others [4,[15][16][17][18][19][20][21][22][23][24][25]. In addition, with the exception of two studies by Oda et al [15] and Yang et al [16], fewer than 200 noncurative gastric ER cases were included in previous studies [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…For example, noncurative gastric ER was defined according to the Japanese gastric cancer treatment guidelines in some studies but was defined according to the original criteria in others [4,[15][16][17][18][19][20][21][22][23][24][25]. In addition, with the exception of two studies by Oda et al [15] and Yang et al [16], fewer than 200 noncurative gastric ER cases were included in previous studies [15][16][17][18][19][20][21][22][23][24][25]. To the best of our knowledge, the present study is the largest study demonstrating the clinical outcomes of more 500 noncurative gastric ESD patients, including long-term survival outcomes with a median follow-up period of more than 5 years and clinicopathological factors associated with metastasis and gastric-cancer-related death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Choi et al [22] also reported that OS and disease-free survival did not differ significantly between patients treated with additional surgical resection and patients simply followed up after ESD in submucosa-invasive gastric cancer. However, this result should be carefully interpreted, because histological analysis demonstrated that the patients who underwent gastrectomy showed significantly higher lymphatic-vascular involvement and deeper submucosal invasion than those followed up without gastrectomy (Table 1), indicating that the patients with these unfavorable histological findings were more frequently selected for additional gastrectomy.…”
Section: Discussionmentioning
confidence: 99%